Determinants of Consumers’ Behavioural Intention and E-Wallet Usage Behavior: Evidence from an Extended UTAUT Model via Structural Equation Modeling - Bui Hong Diep; Dam Tri Cuong (Journal of Applied Data Sciences, 2026)
The rapid proliferation of digital financial technology is speeding up the acceptance of e-wallets as a favoured payment method owing to their simplicity, quickness, and accessibility. Despite the increasing prevalence of e-wallet services, prior research has yielded inconsistent results regarding the factors influencing consumers’ behavioural intentions and actual usage, especially in relation to performance expectancy, effort expectancy, facilitating conditions, trust, and perceived risk. This research enhances the Unified Theory of Acceptance and Use of Technology (UTAUT) model by integrating trust and perceived risk as supplementary antecedents of e-wallet adoption to explain these inconsistencies. Data were gathered using a structured questionnaire sent to 280 e-wallet users in Ho Chi Minh City, Vietnam. The suggested study model was evaluated by Structural Equation Modelling (SEM) to investigate the interrelations among performance expectancy, effort expectancy, social influence, facilitating conditions, trust, perceived risk, behavioural intention, and actual e-wallet use behaviour. The results demonstrate that performance expectancy, social influence, favourable conditions, and trust considerably and favourably affect customers’ propensity to use e-wallets. Moreover, facilitating conditions and behavioural intention were identified as having substantial beneficial impacts on actual e-wallet-using behaviour. In the case of an e-wallet, however, effort expectancy and perceived risk do not have a big effect on behaviour intentions. This research enhances the technology adoption literature by enhancing the explanatory ability of the UTAUT framework within the realm of digital payment systems. The results also offer practical implications for e-wallet providers and digital financial service firms by highlighting the necessity to improve service performance, bolster trust mechanisms, enhance supporting infrastructure, and utilise social influence to promote e-wallet adoption and utilisation.